An Extension of Fermatean b-Derived Fuzzy Soft Ternary Subgroup (Global Journal of Science Frontier Research, 2023)
Soft set, fermatean uncertainty set, n-dimensional, extension, subgroup, k-cut, extension homomorphism, ternary group, b-derived, fermatean uncertainty ternary subgroup.
Keywords: soft set; fermatean uncertainty set; n-dimensional; extension; subgroup; k-cut; extension homomorphism